A scalable corneal xenograft platform: simultaneous opportunities for tissue engineering and circular economic sustainability by repurposing slaughterhouse waste - Wang, Xinyu; Shakeel, Adeeba; Salih, Ahmed E.; Vurivi, Hema; Daoud, Sayel; Desidery, Luca; Khan, Raheema L.; Shibru, Meklit G.; Ali, Zehara M.; Butt, Haider; Chan, Vincent; Corridon, Peter R. (Frontiers in Bioengineering and Biotechnology, 2023)
High-throughput platforms that can generate copious quantities of corneal grafts will be invaluable in addressing the growing global demand for keratoplasty. Slaughterhouses generate substantial underutilized biological waste that can be repurposed to reduce current environmentally unfriendly practices. Such efforts to support ecological sustainability can simultaneously drive the development of transplantable ovine corneas and patient-specific bioartificial keratoprostheses. This study presents a dataset highlighting techniques that pioneered the development of a simplified, inexpensive, and high-throughput corneal xenograft platform. To the best of our knowledge, this is the first dataset to be generated in the United Arab Emirates devised on repurposing slaughterhouse waste in a manner that supports circular economic practices. These efforts outline the first step in developing a platform that can produce dozens of native ovine xenografts and acellular corneal scaffolds that effectively preserve ocular transparency, light transmittance, and ECM components. Based on our characterizations, this research presents key attributes retained in decellularized corneal scaffolds and native xenografts and sets a fundamental stage in the development of tissue engineered keratoprosthesis.